PENGARUH GREEN PRODUCT DAN CUSTOMER PERCEIVED VALUE TERHADAP PURCHASE INTENTION JAM TANGAN KAYU SERIBU SATOE - muhammad aluf ma' lufie; thomas stefanus kaihatu; laij victor effendi (Jurnal Performa)
This research is done to find out The Effect of Green Products and Customer Perceived Value on Purchase Intention of Seribu Satoe Wooden Watch, this research uses quantitative approach with population that is taken from 133 respondents with purposive sampling technique with criteria of Seribu Satoe prospective consumers who have interest in Seribu Satoe wooden watch  and domiciled in Surabaya, Gresik.